2007
DOI: 10.1002/clc.20172
|View full text |Cite
|
Sign up to set email alerts
|

Is Early Cardioversion for Atrial Fibrillation Safe in Patients with Spontaneous Echocardiographic Contrast?

Abstract: The 2006 American Heart Association guidelines for management of patients with atrial fibrillation state: ''For patients with no identifiable thrombus in the left atrium (LA) or left atrial appendage (LAA), cardioversion (CV) is reasonable immediately after anticoagulation with unfractionated heparin. Thereafter, continuation of oral anticoagulation is reasonable for an anticoagulation period of at least 4 weeks.'' For patients with thrombus identified by transesophageal echocardiography, guidelines recommend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
1
21
0
4
Order By: Relevance
“…Finally, it was recently reported that although vitamin E, a naturally occurring lipid-soluble antioxidant, can protect other lipoproteins from oxidation, its incorporation into HDL actually promotes its oxidation [11]. In another recent study, it was also reported that, under certain (genetic) conditions, vitamin E is ineffective in protecting HDL from oxidation and loss of functionality [12]. Thus, the possible roles of lipid-soluble antioxidant compounds, such as VCP, in protecting HDL from oxidative damage and dysfunction remain unresolved.…”
Section: Hypercholesterolemia Cardiovascular Disease Abnormal Glucosementioning
confidence: 97%
“…Finally, it was recently reported that although vitamin E, a naturally occurring lipid-soluble antioxidant, can protect other lipoproteins from oxidation, its incorporation into HDL actually promotes its oxidation [11]. In another recent study, it was also reported that, under certain (genetic) conditions, vitamin E is ineffective in protecting HDL from oxidation and loss of functionality [12]. Thus, the possible roles of lipid-soluble antioxidant compounds, such as VCP, in protecting HDL from oxidative damage and dysfunction remain unresolved.…”
Section: Hypercholesterolemia Cardiovascular Disease Abnormal Glucosementioning
confidence: 97%
“…In mitral stenosis, balloon valvuloplasty will improve the left atrial appendage function and emptying, increasing the flow velocities, and result in resolution of SEC [16]. Similarly in atrial fibrillation, conversion to sinus rhythm often results in resolution of SEC [17]. Maintaining pulsatile flow, either by using a low-dose inotropic agent or reducing the ECMO flow, may help prevent the development of SEC.…”
Section: Commentmentioning
confidence: 99%
“…Häufig stellen sich bei Patienten mit arteriellem Hypertonus oder Krankheitsbildern, die zu einer Verlangsamung des Blutflusses im Vorhof führen (z.B. Mitralstenose, VHF, Vergrößerung des linken Vorhofs, Fibrinogen , Hämatokrit ) sogenannte spontane Echokontraste dar, die mit einem erhöhten Risiko für linksatriale Thromben, thrombembolische Komplikationen und Tod assoziiert sind [27]. Die Prä-valenz von spontanen Echokontrasten bei Patienten mit VHF wird in der Literatur unterschiedlich hoch zwischen 12 und 67% beschrieben [27].…”
unclassified
“…Mitralstenose, VHF, Vergrößerung des linken Vorhofs, Fibrinogen , Hämatokrit ) sogenannte spontane Echokontraste dar, die mit einem erhöhten Risiko für linksatriale Thromben, thrombembolische Komplikationen und Tod assoziiert sind [27]. Die Prä-valenz von spontanen Echokontrasten bei Patienten mit VHF wird in der Literatur unterschiedlich hoch zwischen 12 und 67% beschrieben [27]. Nicht selten wird bei Patienten mit spontanen Echokontrasten von einer "frühen" Kardioversion abgesehen und der Patient zunächst für mindestens 4 Wochen therapeutisch antikoaguliert, bevor -nach neuerlicher transösophagealer Echokardiographie und Ausschluss von spontanen Echokontrasten -"verzö-gert" eine Kardioversion durchgeführt wird.…”
unclassified
See 1 more Smart Citation